The impact of parity on the risk of nonalcoholic fatty liver disease defined by hepatic steatosis index: A nationwide cohort study - So-hyeon Hong; Soon Young Hwang; Ji Hee Yu; Nam Hoon Kim; Hye Jin Yoo; Ji A Seo; Sin Gon Kim; Nan Hee Kim; Sei Hyun Baik; Kyung Mook Choi (Scientific Reports)
Abstract Despite the impact of pregnancy and parity on the prevalence of metabolic diseases, there are limited epidemiologic data regarding the association between parity and nonalcoholic fatty liver disease (NAFLD). We examined the association between parity, parity number, and NAFLD risk in pre- and postmenopausal women using data representing the entire Korean population. This cohort included 28,003 women (13,145 premenopausal and 14,858 postmenopausal) from the Korean National Health and Nutrition Examination Survey. NAFLD was defined by the hepatic steatosis index. Multivariable logistic regression analysis was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs). The prevalence of NAFLD was 21.0% (15.3% in premenopausal women and 26.1% in postmenopausal women). In premenopausal women, parity increased the odds of NAFLD in the unadjusted model (OR 1.72, 95% CI 1.49–2.00), but after adjustment for potential confounders, including obesity, it exhibited a protective effect (OR 0.61, 95% CI 0.46–0.80). This finding was consistent when participants were divided into low parity (1–2 births) and high parity (3 or more births) groups (OR 0.59, 95% CI 0.45–0.79, and OR 0.64, 95% CI 0.47–0.87, respectively). In postmenopausal women, there was no significant statistical association between parity and NAFLD. These findings remained consistent across several sensitivity analyses excluding potential risk factors and in subgroup analyses. After adjusting for various confounding parameters, including obesity, parity was associated with a lower risk of NAFLD in premenopausal women. This suggests a protective effect of parity on NAFLD in premenopausal women, provided that appropriate body weight and other metabolic risk factors are maintained after delivery.